Supersonic, four shock, ramp type intake design, with internal boundary layer bleed - Van Staden, Paul Arnold (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Eng. (Aeronautics)) -- University of Stellenbosch, 1990.